2015
DOI: 10.1111/joor.12310
|View full text |Cite
|
Sign up to set email alerts
|

Validity of self‐reported sleep bruxism among myofascial temporomandibular disorder patients and controls

Abstract: Sleep bruxism (SB), primarily involving rhythmic grinding of the teeth during sleep, has been advanced as a causal or maintenance factor for a variety of orofacial problems, including temporomandibular disorders (TMD). Since laboratory polysomnographic (PSG) assessment is extremely expensive and time-consuming, most research testing this belief has relied on patient self-report of SB. The current case-control study examined the accuracy of those self-reports relative to laboratory-based PSG assessment of SB in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
76
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 27 publications
1
76
1
5
Order By: Relevance
“…First, its low sensitivity and specificity cause There was no significant difference in the distribution of EMG activity per hour between males and females. The percentage of subjects who had more than 25 episodes of EMG activity per hour was 6.6 % [14,24]. Since sleep bruxism may involve not only grinding but also clenching of teeth, sleep bruxism might be soundless.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, its low sensitivity and specificity cause There was no significant difference in the distribution of EMG activity per hour between males and females. The percentage of subjects who had more than 25 episodes of EMG activity per hour was 6.6 % [14,24]. Since sleep bruxism may involve not only grinding but also clenching of teeth, sleep bruxism might be soundless.…”
Section: Discussionmentioning
confidence: 99%
“…However, the theories that propose a genetic predisposition to sleep bruxism stem mostly from studies based on self-administered questionnaires. A polysomnographic study reported that self-report is highly unlikely to be a valid indicator of true sleep bruxism because of its low sensitivity and specificity estimated at less than 70 and 50 %, respectively [14]. The other twin study evaluated bruxism based on facet patterns and showed rate of concordance being higher in monozygotic twins than in dizygotic twins [15].…”
Section: Introductionmentioning
confidence: 98%
“…We recognize that self-reports have a limited capacity to detect true presence of SB in blood relatives. 3,34 In conclusion, due to the large population surveyed, this study should represent a landmark in the field of sleep bruxism and should open the door for future studies on comorbidities between SB, sleep maintenance, gender, and chronic pain. This study should also present an argument in favor of future investigations of the genetics of SB.…”
mentioning
confidence: 99%
“…The sensibility and accuracy of parents' report of sleep bruxism are low, however, it shows excellent specificity when compared with polysomnographic findings 16 . The reliability of the questionnaire-based assessment of SB has been questioned 16 and its use has been of concern to several authors, both in studies involving adults 17,18 and children 3,16 . Despite its obvious limitations, the parental reports of SB remain important for epidemiological studies with large samples.…”
Section: Discussionmentioning
confidence: 99%